2017
DOI: 10.31018/jans.v9i3.1452
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in CMS backcross generations and their maintainers in eggplant (Solanum melongena L.)

Abstract: Twelve genotypes of eggplant in BC 3 , BC 4 and BC 5 generations of CMS-lines derived from Solanum aethiopicum × Solanum melongena cross along with their maintainers were evaluated for eighteen quantitative characters at Punjab Agricultural University Ludhiana. Analysis of variance depicted significant variation (P ≤ 0.05) for all the characters in all generations. High PCV and GCV values were observed for fruit length, fruit girth, fruit weight, number of fruits plant -1 and yield plant -1 in all generations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These differences in traits between genotypes are explained by a difference in the genetic factors carried by each genotype, in addition to the extent to which each genotype responds to the environment in which it is cultivated. These results agree with the findings that have been discovered by Kummer et al,(16),Mehraj et al,(19), Akpan et al,( 1), Garcha et al, (12),Patel et al,(24), Robinson(28) and Sawadogo et al,(29) Whose reported that the genotypes of the eggplant differed in the vegetative growth and yield characteristics.…”
Section: Analysis Of Sources Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…These differences in traits between genotypes are explained by a difference in the genetic factors carried by each genotype, in addition to the extent to which each genotype responds to the environment in which it is cultivated. These results agree with the findings that have been discovered by Kummer et al,(16),Mehraj et al,(19), Akpan et al,( 1), Garcha et al, (12),Patel et al,(24), Robinson(28) and Sawadogo et al,(29) Whose reported that the genotypes of the eggplant differed in the vegetative growth and yield characteristics.…”
Section: Analysis Of Sources Variationsupporting
confidence: 92%
“…The number of fruits in each one of the plants had positive and significant correlations with the number of branches in each one of the plants, the number of leaves in each one of the plants, and the height of the plant, applications of breeding methodology will improve the productivity of these eggplant genotypes since there is an existence of genetic variability among genotypes as progress in breeding depends on this variation. Garcha et al, (12) indicated in their study the variance analysis, which had depicted significant variations (i.e., P ≤ 0.05) for every character in each generation, high value in the values of the GCV and PCV have been noticed for the length of the fruit, the weight of the fruit, girth of the fruit, yield in each one of the plants and number of the fruits in each one of the plants in all of the generations, which indicated high germplasm variability. High heritability in combination with high genetic advances has been discovered for the peduncle length, fruit girth, fruit length, number of fruits in each one of the plants, fruit weight, and yield in each one of the plants in every generation, which indicates the dominance of the additive actions of the genes for those features.…”
Section: Introductionmentioning
confidence: 98%
“…Restorer lines are used as a male parent to develop male fertile F1 hybrids for commercial production. Punjab Agricultural University has also developed different male sterile lines, their respective maintainers, and restorer lines for utilization in heterosis breeding (Garcha et al 2017, Kaur et al 2021. Further, the identification of the most appropriate male sterile and fertility restorer combinations is necessary for utilization at commercial production.…”
Section: Introductionmentioning
confidence: 99%